Effectiveness of self-assembling peptide P11-4 as a minimally invasiveintervention for initial smooth-surface carious lesions in permanentteeth: A case report (Indian Journal of Case Reports, 2026)
White spot lesions (WSLs) are the earliest visible manifestation of enamel caries and present significant esthetic concerns, particularly in adolescents. Conventional treatments, such as fluoride, casein phosphopeptide-amorphous calcium phosphate, and resin infiltration, have limitations, including incomplete remineralization or irreversible enamel alteration. Self-assembling peptide P11-4 (SAP P11-4; Curodont Repair, Credo AG, Switzerland) is a biomimetic material that promotes subsurface hydroxyapatite formation within the lesion body. A 16-year-old female presented with International Caries Detection and Assessment System 1–2 WSLs on the labial surfaces of teeth 11, 12, 21, and 22. Clinical examination excluded fluorosis, enamel hypoplasia, and post-orthodontic demineralization. Following surface preparation, SAP P11-4 was applied under rubber dam isolation. The procedure was well tolerated, with no adverse events. Progressive reduction in lesion opacity was observed, with favorable esthetic and structural outcomes maintained at 1 year, supporting SAP P11-4 as a minimally invasive treatment option.